Pembuatan Game Edukasi Pengenalan Flora dan Fauna Indonesia - Hartono, Leonardy; Purba, Kristo Radion; Palit, Henry Novianus (Jurnal Infra, 2015)
The games industry has been growing rapidly as attested by their increase in numbers and varieties (genres),sophisticated graphic display, and rich features. Not only are the gamesplayed by adolescents but they are loved by children, too. However, most games played by children do not help to educate them.For that reason, we propose an educational game to introduce the florae and faunae of Indonesia. It is an adventure game, exploring the islands of Indonesia. Information will be given for every flora or fauna found during the exploration. The game has âsave and loadâ features and can record the floraeand faunaecollected.The game has been tested on different computers (with different specifications). It was found that the game can run smoothly on computers fulfilling the minimum requirements.